HUBUNGAN POWER OTOT TUNGKAI DENGAN AKURASI SMASH JUMP DALAM PERMAINAN BULUTANGKIS PADA CLUB PUTRA PB. PRATAMA KOTA PEKANBARU - Peny Nurhayati; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this study is the Club Putra PB. Pratama City of Pekanbaru when training leg muscle strength with an accurate smash jump is considered deficient ie the jumps are not too optimal when doing a smash jump and the shuttlecatch is not right on target towards the opponent's field, smash punches he is an opponent that can be exchanged Shuttlecock can quickly shuttlecock positions that do smash jump Limbs with Smash Jump Accuracy in Badminton Games at PB Putra Club. Primary City of Pekanbaru. This research was conducted in the badminton pratama field in Pekanbaru City, Riau Street. When this research was conducted in December 2018 until November 2019. The entire population was sampled (total sampling), as many as 10 people. Based on the results of research and data processing using research procedures it can be concluded that there is a variable for the relationship X with Y variables obtained rcount = 0.953> rtable = 0.798 then the relationship between variable X and Y variable is needed. Thus Ho can be accepted and supported. accepted at the level ɑ = 0.05 in other words there is a significant relationship between leg muscle strength and smash jump accuracy in the Putra Putra Badminton Club PB Pekanbaru City. Key Words: Leg Muscle Power, Smash Jump Accuracy.